1998
DOI: 10.1007/s11663-998-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

A correlation to describe interfacial heat transfer during solidification simulation and its use in the optimal feeding design of castings

Abstract: It is known from experimental data that for pure aluminum castings manufactured via the gravity die casting process, the interfacial heat-transfer coefficient can vary in the range 500 to 16,000 W/m 2 K. These coefficients are of significant importance for the numerical simulation of the solidification process. The experimentally determined variation of interfacial heat-transfer coefficients with respect to time has been recalculated to highlight the variation with respect to casting temperature at the interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Lewis and Ransing [21] Santos et al [18] This study Comparisons between the experimental temperature and the predicted temperature in other locations are shown in Fig. 14.…”
Section: Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…Lewis and Ransing [21] Santos et al [18] This study Comparisons between the experimental temperature and the predicted temperature in other locations are shown in Fig. 14.…”
Section: Modelmentioning
confidence: 92%
“…The other two models proposed by Santos et al [18] and Lewis and Ransing [21] are also tested to calculate the IHTC, and the optimization results are given in Table 3. The corresponding temperature calculated at thermocouple 1 is shown in Fig.…”
Section: The Metal Casting-mould Ihtcmentioning
confidence: 99%
“…The IHTC value can be modelled as a function of casting temperature at metal-mould interface [20] or as a function of air gap formation at the interface [21,22]. Lewis and Ransing [23] proposed a correlation and presented that variation in IHTC with respect to interface temperature is exponential in nature. Prasanna kumar and Kamath [24] showed that heat flux at interface depends upon casting geometry.…”
Section: Previous Workmentioning
confidence: 99%
“…Then the air gap width is related to interfacial heat transfer coefficient by a 'user defined' equation. Later, Lewis et al proposed a correlation [10][11][12] to adjust the interfacial heat transfer coefficient with respect to casting interface temperature. Researchers have been numerically and experimentally studied the effect of gap on heat transfer for different alloys [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%